SADF soldiers’ silences: institutional, consensual and strategic - Baines, Gary (Acta Academica: Critical views on society, culture and politics, 2015)
This article treats silence as a collective phenomenon. Silence can be proscribed and enforced, socially conditioned and sanctioned, or voluntarily embraced. All forms were evident in the case of soldiers who served in the South African Defence Force (SADF). First, they acquiesced to an institutional silence imposed upon them regarding their role in waging a war in Angola/Namibia, as well as suppressing the struggle against apartheid. Secondly, SADF veterans were complicit in a self-imposed and consensual silence about human rights abuses following the country’s democratisation. This was partly enabled by a ‘pact of forgetting’ struck by the political elites and leaderships of the statutory and non-statutory forces. Finally, SADF veterans have employed silence as a strategy of control; they have invoked their experiential knowledge of the ‘Border War’ to assert their authority to tell the ‘truth’, thereby constructing a narrative of the conflict that remains largely unchallenged in the public domain. Consciously or unconsciously, SADF soldiers contributed to the public construction of silence following the violence of the apartheid wars.